Peri-prosthetic Bone Mineral Density Measurements of the Proximal Femur in Hip Arthroplasty - Takasu, Noriyuki; Nakamura, Kosaku; Yamamoto, Kichizo; Morimoto, Kanehito; Kishimoto, Hideaki; Nagashima, Hideki (Orthopedics & Traumatology, 1994)
Peri-prosthetic bone mineral density (BMD) was determined using dual X-ray absorptiometry (DXA) (LUNAR DPX). Thirty-three uncemented primary unilateral hip arthroplasties were performed in 33 patients with a mean age of 57.1 years, 26 hips for osteoarthritis and 7 for aseptic femoral head necrosis, with one to 70 months' follow up. The types of prosthesis were Omnifit for 8 hips and Omniflex for 25 hips. The areas measured were Gruen's 7 zones around the femoral prosthesis. Both the operated and contralateral femurs were measured in each patient and the BMD values expressed as BMD ratio (operated/contralateral). The coefficient of variation in BMD determined in 6 subjects was 1.9%. In the cross sectional study, a decrease in BMD ratio as observed at zone 1, 2 and 7. The results suggest that bone loss around proximal prostheses occurs gradually after surgery.